Multi-periodic climate dynamics: spectral analysis of long-term instrumental and proxy temperature records - H.-J. Lüdecke; A. Hempelmann; C. O. Weiss (Climate of the Past, 2013)
The longest six instrumental temperature records of monthly means reach back maximally to 1757 AD and were recorded in Europe. All six show a V-shape, with temperature drop in the 19th and rise in the 20th century. Proxy temperature time series of Antarctic ice cores show this same characteristic shape, indicating this pattern as a global phenomenon. We used the mean of the six instrumental records for analysis by discrete Fourier transform (DFT), wavelets, and the detrended fluctuation analysis (DFA). For comparison, a stalagmite record was also analyzed by DFT. The harmonic decomposition of the abovementioned mean shows only six significant frequencies above periods over 30 yr. The Pearson correlation between the mean, smoothed by a 15-yr running average (boxcar) and the reconstruction using the six significant frequencies, yields r = 0.961. This good agreement has a > 99.9% confidence level confirmed by Monte Carlo simulations. It shows that the climate dynamics is governed at present by periodic oscillations. We find indications that observed periodicities result from intrinsic dynamics.